2017
DOI: 10.1002/jrs.5277
|View full text |Cite
|
Sign up to set email alerts
|

Submicron Raman spectroscopy mapping of serpentinite fault rocks

Abstract: Submicron Raman spectroscopy mapping is able to unambiguously distinguish the main serpentine minerals within their in situ microstructural context. The high spatial resolution (~370 nm), large‐area coverage (up to hundreds of micrometres in each dimension), and ability to map directly on polished thin sections allows novel interpretations to be made regarding the nature and evolution of serpentinite fault rock textures. The potential of this method is illustrated by examining submicron‐scale textures of scaly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
42
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 34 publications
(47 citation statements)
references
References 50 publications
5
42
0
Order By: Relevance
“…Submicron Raman spectroscopy mapping was performed on an Alpha 300R+ confocal Raman microscope (WITec GmbH, Ulm, Germany) in the Chemistry Department at the University of Otago, New Zealand. A dry 100× objective (Zeiss), 1,200 g mm −1 grating and a 532‐nm laser (Coherent, Santa Clara, California) at 25 mW were used, resulting in a laser spot size of approximately 370 nm . A nano‐piezo stage was used to control the sample position during the Raman mapping process.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…Submicron Raman spectroscopy mapping was performed on an Alpha 300R+ confocal Raman microscope (WITec GmbH, Ulm, Germany) in the Chemistry Department at the University of Otago, New Zealand. A dry 100× objective (Zeiss), 1,200 g mm −1 grating and a 532‐nm laser (Coherent, Santa Clara, California) at 25 mW were used, resulting in a laser spot size of approximately 370 nm . A nano‐piezo stage was used to control the sample position during the Raman mapping process.…”
Section: Methodsmentioning
confidence: 99%
“…Raman spectroscopy has previously been used for rapid and cost‐effective identification of the most common serpentine minerals: lizardite, chrysotile, and antigorite . The high‐wavenumber region (3,600–3,710 cm −1 ) of the Raman spectra has been shown to be the most useful for distinguishing these serpentine mineral types . In this region, the well‐defined Raman spectra arise from inner and outer hydroxyl vibrations, due to the occurrence of Mg (OH) 2 brucite‐like octahedral sheets.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Rooney et al reported submicron Raman spectroscopy mapping of serpentinite fault rocks. The potential of their method is illustrated by examining submicron‐scale textures of scaly serpentinites from a lithospheric‐scale shear zone in New Zealand and a subduction‐related serpentinite body in California, USA . Secchi et al described mineralogical investigations using X‐ray powder diffraction, X‐ray fluorescence, and Raman spectroscopy in a combined approach.…”
Section: Solid‐state Studiesmentioning
confidence: 99%